JARGONS USED BY INDONESAN AND MALAYSIAN THRIFTERS - Andry Azhari (LINGUA LITERA : journal of english linguistics and literature, 2026)
This research aimed to discuss the meaning and forms of jargons used by thirfters especially in Indonesia and Malaysia. Jargons have been used by several communities and they might not be understood by the outside circle of the community. Thrifters is one of the communities that have created and regularly used their own jargons that might not be understood by by others outside their circle. This research was conducted by using qualitative method. The data of this research was taken from an observation to some thrifters communities in West Sumatera. The researcher used Geoffrey leech’s theory to analyze the meaning of the jargons and Halinggan’s Theory to analyze the forms of jargons. There were 40 jargons found in this research. All types of meaning described by leech can be found from the jargons. Moreover, form four forms of jargons, only acronym cannot be found from the Jargons. The others such as word, phrase, and abbreviation can be found in this research. In other words, this research aims to identify and analyze the jargons used by thrifters (individuals passionate about hunting for original branded secondhand clothes) in Malaysia and Indonesia. Specifically, the study focuses on investigating both the linguistic forms and the contextual meanings of the specialized expressions such as Bundle, barang kaki, crack manja, ekor ball, and AOP frequently employed within the thrifting community. By documenting and analyzing these specific terms, this study seeks to bridge the communication gap between insiders and outsiders of the thrifting subculture, ultimately providing additional linguistic and cultural knowledge to the general public.